Między nami sąsiadami… Obcy, cudzoziemiec – stosunek studentów do obywateli Ukrainy - Guzy-Steinke, Halina (Kultura-Społeczeństwo-Edukacja, 2020)
The article presents a part of research on the students’ attitude towards foreigners, in particular Ukrainian citizens. In Poland it is currently the largest group of foreigners, as well as the largest group of foreign students studying at Polish universities. The text contains references to the sociological concept of „foreign”, especially to G. Simmel’s, and also to the category of „stereotype”, which is usually associated with the perception of different nationalities. The presented fragment of research compares the attitude of students to the stereotype of a Ukrainian, which has been acknowledged and consolidated in Poland over the years of common history. Respondents also rated functioning of Ukrainian acquaintances at the university and in the dorm. Respondents in their opinion claim that the group of Ukrainians is large, but it is almost invisible at the university. This is due to the low access of foreigners to student life and isolation among „their own”. The attitude of Polish youth is certainly significant for this type of behavior. Polish students, despite declarations, do not make enough effort to get to know and maintain closer contacts with colleagues from Ukraine.